DIVERSIFIKASI KOMODITAS PANGAN UNGGULAN LOKAL BERBASIS AGROPOLITAN DI DAERAH KABUPATEN SLEMAN D.I.YOGYAKARTA - Nur Feriyanto; Ilya Fadjar Maharika; Feris Firdaus (Teknoin, 2017)
The development of agropolitan areas can deny the false assumption that the developed regions are transformed into urban areas and changes in the dominant role of the agricultural sector to the industrial sector, and services. Assuming that the agricultural sector calculates downstream production up to agro-processing activities, an area can be called advanced by still characterizing the rural areas and the dominant role of the agricultural sector. Based on the results of analysis of excellent potential characteristics with the Sleman region then determined superior food commodities supported by many other commodities. The pre-eminent food commodities are salak fruit located in Turi District and freshwater fish commodities bred in ponds located in Ngemplak sub-district. The two leading food commodities can then be developed into superior products supported by various other food products in order to produce various kinds of food diversification to improve the agropolitanbased rural economy. Based on the results of SWOT analysis related to the potential superior characteristics with the Sleman region then determined superior food commodities supported by many other commodities. The pre-eminent food commodities are salak fruit located in Turi District and freshwater fish commodities bred in ponds located in Ngemplak sub-district. The two leading food commodities can then be developed into superior products supported by various other food products in order to produce various kinds of food diversification to improve the agropolitan-based rural economy. Examples of derivatives of salak pondoh products are salak chips, dodol salak, salak syrup, candied salak, coffee seeds bark and others. Examples of innovations that have been developed is the diversification of catfish and tilapia into catfish abon, catfish chips, crispy tilapia, fish crackers and others that have the durability / durability up to a year more in packaging